Mate Choice and Copulation Frequency in the Burying Beetle Nicrophorus quadripunctatus (Coleoptera: Silphidae): Effect of Male Body Size and Presence of a Rival - Seizi Suzuki (Psyche: A Journal of Entomology)
It is widely assumed that there exists a competition between males for mating and that females prefer males with elaborate male traits. Further, such traits are considered to be synonymous with high quality in terms of benefits to females. The number and duration of copulations and the frequency of mate refusal between large and small Nicrophorus quadripunctatus males were examined both for single males and for two males competing. The number of copulations was not affected by the size of the male or by the presence of a rival, but there was a significant interaction such that large males increased their number of copulations when a small rival was present. Copulation duration was not affected by male size but was shortened by a rival male. Females rejected copulation attempts of small males more often than of large males, whether the males were alone or paired with a rival. These results suggest that large males have two advantages: they win contests between males and are preferred by females.